2016
DOI: 10.1111/joss.12237
|View full text |Cite
|
Sign up to set email alerts
|

Development of a “living” lexicon for descriptive sensory analysis of brewed coffee

Abstract: Coffee is one of the most common beverages in the world. However, a sensory lexicon for determining descriptive differences resulting from breeding, agronomic, processing, storage, and brewing modifications is needed. This study developed a sensory lexicon for brewed coffee. More than 100 different coffee samples from 14 countries around the world were used to create this lexicon in four Phases. A highly trained panel assessed all coffee samples using descriptive analysis.The sensory panel identified 110 attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 21 publications
5
117
0
1
Order By: Relevance
“…Every attribute in the lexicon has a definition and between one and three references. Many of the attributes (smoky, ashy, woody, musty/dusty, musty/earthy, burnt, pungent, petroleum‐like, bitter, metallic, and sour) are commonly used and already had definitions and references that were used in other published lexicons (e.g., Chambers IV et al, ; Retiveau et al, ; Talavera & Chambers, ). Some of those terms needed to be modified to better suit this lexicon, such as the overall smoky reference that was better defined by a different liquid smoke product and burnt, which needed a better defined process (based on peanuts and used in a coffee lexicon (Chambers IV et al, )) for creating the reference that produced a more consistent reference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Every attribute in the lexicon has a definition and between one and three references. Many of the attributes (smoky, ashy, woody, musty/dusty, musty/earthy, burnt, pungent, petroleum‐like, bitter, metallic, and sour) are commonly used and already had definitions and references that were used in other published lexicons (e.g., Chambers IV et al, ; Retiveau et al, ; Talavera & Chambers, ). Some of those terms needed to be modified to better suit this lexicon, such as the overall smoky reference that was better defined by a different liquid smoke product and burnt, which needed a better defined process (based on peanuts and used in a coffee lexicon (Chambers IV et al, )) for creating the reference that produced a more consistent reference.…”
Section: Resultsmentioning
confidence: 99%
“…Most researchers described smoked flavor as smoky (Bárcenas et al, ; Smiecinska and Chwastowska, ), smoked (Almli and Hersleth, ; Carrapiso et al, ; Kostyra et al, ; Petridis et al, ; Portella et al, ), or smoke (Brillet et al, ; Cardinal et al, ; Midelet‐Bourdin et al, ; Mørkøre et al, ; Stojković et al, ) for specific products. However, authors also indicated the smoked flavor could be described as artificial (Portella et al, ), bitter (Almli and Hersleth, ; Portella et al, ), tart (Smiecinska and Chwastowska, ), vegetal and herb (Midelet‐Bourdin et al, ; Séménou et al, ), rubber (Brillet et al, ; Midelet‐Bourdin et al, ), wood fire (Cardinal et al, ; Mørkøre et al, ; Séménou et al, ), and pungent (Bárcenas et al, ) There are a few researchers that have reported smoked flavor definitions and references as part of other lexicons (e.g., coffee, Chambers IV et al, ; soy sauce, Inamura, ; Pujchakarn, Suwonsichon, & Suwonsichon, ; sausage, Pereira et al, ), but these typically were one to three terms and suggest the potential need to establish a general lexicon to describe smoked flavor characteristics. Such general lexicons have been published previously for other flavor components such as green (Hongsoongnern & Chambers IV, ), beany (Bott & Chambers IV, ), and nutty (Miller, Chambers IV, Jenkins, Lee, & Chambers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Panelists were selected based on their interest and availability, but also correct discrimination of four or more coffee pairs as described in section “Coffee service.” Each panelist attended five training sessions over a 2‐week period. During the initial two sessions, attribute generation was completed with the assistance of the Coffee Taster's Flavor Wheel (Chambers et al., ; Spencer, Sage, Velez, & Guinard, ). Consensus terminology and reference standards (Table ) were developed over the next three training sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Panelists were then trained and their performance assessed according to ISO 11132 (ISO, ). Finally, they were requested to evaluate the samples in order to validate the developed lexicon (Chambers et al, ; Lawless & Civille, ). Tastings were held in tasting booths under white light (6500 K) and controlled temperature (20–22°C).…”
Section: Methodsmentioning
confidence: 99%